Organizacyjno-prawne problemy zabezpieczania zasobów intelektualnych w przedsiębiorstwie - Dereń, Aldona Małgorzata; Skonieczny, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The goal of the research paper is to present intellectual property as an intangible resource in enterprise. The specific features of this resource and the base of competing (co-operation and rivalry) characteristic for a contemporary market make these core resources for development of not only a large company. In these circumstances it is a premise to create adjusted orientation on the search and exposure of immaterial values (but also their monitoring of competitors). Simultaneously this orientation is aimed at the choice of proper manners of protection of these values both within the organization, in the process of sharing both knowledge and information with other organizations on the market
Keywords: własność intelektualna; zasoby strategiczne; wiedza; informacja